2010
DOI: 10.1111/j.1759-5436.2010.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Quotas as a Path to Parity: Challenges to Women's Participation in Politics

Abstract: The promise of democratic equality has not arrived for women. In all societies said to be democratic, women have had an arduous struggle and are still fighting for access to rights common to any male citizen, for example an equal salary for equal work, promotion opportunities, the right to physical integrity, and access to work. Gaining the right to vote and the right to run for office as elected representatives has not in practice meant the right to be elected under the same conditions as men (Petit 2007). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar processes of feminist constituency-building are evident in Costa's repeat surveys of local councillors which show between 1992 and 2012 an increase from 3.1 to 13.8 per cent of those reporting a desire to represent and help women as their motive for entering politics (Costa 2014). Alongside this there was little change in women's perceptions of support from their parties, a perception backed up by Costa's (2010) analysis of how professed support by political parties for parity in politics vanishes in practice into a string of broken commitments. In this picture, the role played by women's movements in mobilizing demand, amplifying voice and opening up opportunities for women's political apprenticeship is an important constant.…”
Section: Box 4: Brazil's Feminist Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar processes of feminist constituency-building are evident in Costa's repeat surveys of local councillors which show between 1992 and 2012 an increase from 3.1 to 13.8 per cent of those reporting a desire to represent and help women as their motive for entering politics (Costa 2014). Alongside this there was little change in women's perceptions of support from their parties, a perception backed up by Costa's (2010) analysis of how professed support by political parties for parity in politics vanishes in practice into a string of broken commitments. In this picture, the role played by women's movements in mobilizing demand, amplifying voice and opening up opportunities for women's political apprenticeship is an important constant.…”
Section: Box 4: Brazil's Feminist Schoolsmentioning
confidence: 99%
“…Much depends on the electoral system (Ballington 2012) and on political parties. In Costa Rica, Sagot's research revealed how political parties grudgingly accepted a 40 per cent quota and then employed counter-strategies to avoid it being implemented (Sagot 2010); in Brazil, Costa found a lack of effective sanctions to enforce compliance and of support to women candidates from political parties (Costa 2010(Costa , 2014. Research in Sierra Leone revealed the extent to which women candidates face violence and intimidation (Abdullah 2010(Abdullah , 2014.…”
mentioning
confidence: 99%